Information Sources, their Utilization Pattern vis-à-vis Mithun (Bos frontalis) Husbandry in Arunachal Pradesh - Biam, Kamni P.; Devi, L. Sunitibala; Khate, K.; Singh, N. Uttam; Paul, Pampi; Gowda, C. (Indian Journal of Extension Education, 2022)
The study was designed to assess the utilization pattern of mithun husbandry information sources by the mithun farmers in the state of Aruncahal Pradesh during 2019-20. Using multi-stage stratified random sampling a total of 120 farmers who owned and reared mithuns was selected. The study compared the utilization pattern of different sources and channels used by the farmers. Overall, the major source of channel of the mithun for any information on mithun management and production was their fellow mithun friends, followed by television and internet. The indigenous knowledge played a prime source for mithun husbandry information. Multiple regression analysis was employed to find out the independent variables that simultaneously contributed the information utilization pattern. Age of the household head, years of formal education, annual income from mithun and annual income significantly contributed in influencing the information utilization pattern. The mithun farmers of Aruncahal Pradesh used both the traditional as well as modern tools to access the mithun management and production information.
Keywords: Information utilization pattern; Mithun farmers; Mithun husbandry; Regression